2016
DOI: 10.1016/j.jhep.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol stimulates macrophage activation through caspase-dependent hepatocyte derived release of CD40L containing extracellular vesicles

Abstract: Background/Aims The mechanisms by which hepatocyte exposure to alcohol activates inflammatory cells such as macrophages in alcoholic liver disease (ALD) are unclear. The role of released nano-sized membrane vesicles, termed extracellular vesicles (EV), in cell-to-cell communication has become increasingly recognized. We tested the hypothesis that hepatocytes exposed to alcohol may increase EV release to elicit macrophage activation. Methods Primary hepatocytes or HepG2 hepatocyte cell lines overexpressing et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
189
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 193 publications
(199 citation statements)
references
References 49 publications
10
189
0
Order By: Relevance
“…Whether this mechanism also contributes to caspase-1-induced MP release in our E10d + 1B model required further studies. In addition, activation of the caspase apoptotic pathway (caspase-3 and caspase-8) promotes MP release in several types of cells, including neutrophils (37), adipocytes (38), and hepatocytes (21). It will be interesting to investigate whether caspase-1 activation of pyroptosis, a type of programed cell death that is different from apoptosis (39), also contributes to MP formation and release.…”
Section: Shown Scale Bar: 100 μM Arrows Indicate Mpo+ Cells (D-h) Wmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether this mechanism also contributes to caspase-1-induced MP release in our E10d + 1B model required further studies. In addition, activation of the caspase apoptotic pathway (caspase-3 and caspase-8) promotes MP release in several types of cells, including neutrophils (37), adipocytes (38), and hepatocytes (21). It will be interesting to investigate whether caspase-1 activation of pyroptosis, a type of programed cell death that is different from apoptosis (39), also contributes to MP formation and release.…”
Section: Shown Scale Bar: 100 μM Arrows Indicate Mpo+ Cells (D-h) Wmentioning
confidence: 99%
“…Blockage of the CXCL1 receptor CXCR1/2 ameliorated alcoholic steatohepatitis in mice (14). In addition to chemokines, extracellular vesicles (EVs) are new players in cellto-cell communication and play an important role in promoting inflammation and neutrophil infiltration in a variety of diseases (15,16), including liver diseases (17)(18)(19)(20)(21)(22)(23)(24)(25). EVs are nanometer-sized, membrane-bound extracellular milieu vesicles derived from cells (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a very recent study, MV have now been identified as an important pathomechanism in early ethanol-induced damage and as a novel form of crosstalk between hepatocytes and liver-resident macrophages. Verma et al [92] could show that ethanol results in the release of MV from hepatocytes via activation of the pro-apoptotic protein caspase 3. These MV have further been shown to stimulate macrophage activation by CD40 ligand-a member of the TNF family-and to induce inflammatory cytokines leading to liver inflammation [92].…”
Section: From Injury To Inflammation In Alcoholic Hepatitismentioning
confidence: 99%
“…In NASH, EV cargoes include the proinflammatory chemokine CXCL10, which recruits macrophages, and TRAIL, which activates macrophages through death receptor signaling and leads to increases in IL-1β and IL-6 (65, 100, 101). In ALD, CD40 ligand-containing (CD40L-containing) EVs are released by hepatocytes and, in turn, activate CD40 on macrophages, which induces proinflammatory signaling (102). Sphingolipid cargoes, specifically C16:0 ceramide and sphingosine 1-phosphate (S1P), on EVs are implicated in the recruitment of macrophages to the steatotic liver in NASH (103).…”
Section: Similar Pathophysiological Concepts Of Nash and Ash With CLImentioning
confidence: 99%